High rheumatoid factor does not diminish efficacy of TNF inhibitors in seropositive JIA - Boris Hügle; Gerd Horneff; Johannes-Peter Haas (Pediatric Rheumatology Online Journal)
Abstract Objectives Rheumatoid factor (RF) binds to the immunoglobulin Fc portion, which might influence the efficacy of Fc-carrying TNF inhibitors (TNFi). This has been shown in studies in adults with RF-positive RA, but not yet in children. The aim of this study was to determine efficacy of TNFi in children with seropositive polyarthritis according to rheumatoid factor levels. Methods Two databases were searched for patients with JIA/seropositive polyarthritis, admitted between November 2009 and March 2023. Data collected were demographic data, treatment with antirheumatic medications and JADAS27 and cJADAS27 prior to and after start of TNFi treatment. Changes in JADAS27 and cJADAS27 on TNFi were compared between patients with highly elevated RF (> 160 U/ml) and low titre RF (< 160 U/ml) using repeated measures ANOVA. Results 28 patients were included, 16 with RF < 160 U/ml at diagnosis, and 12 with RF ≥ 160 U/ml. 21 patients (75%) were treated with etanercept, three (11%) with adalimumab and four (14%) with golimumab, 23 patients additionally received methotrexate. Mean JADAS27 (cJADAS27) at treatment start was 23.0 ± 14.7 (21.0 ± 12.1), and 4.8 ± 5.0 (4.8 ± 4.7) at assessment after starting TNFi. Independent-samples t-test comparing percentage improvement as well as an ANCOVA determined that mean JADAS27 and cJADAS27 scores did not differ significantly across the two time points. Conclusions Unlike in adults, efficacy of TNFi was not diminished by elevated levels of RF in this cohort of pediatric patients with seropositive polyarthritis. Further studies are necessary to confirm these findings.